Jebakan Waktu: Peran Deiksis Temporal dalam Membangun Suspense Novel I’m Not Stupid - Arsyi Aisyah; Siti Nur Aprilianti; Didin Komarudin (Universitas Insan Budi Utomo, 2026)
This study examines the role of Temporal Deixis in building suspense in the thriller novel I’m Not Stupid using a qualitative-descriptive approach. Data were collected through close reading and analyzed using the interactive model of Miles, Huberman, and Saldaña to identify the form, narrative function, and contribution of time markers in the storyline. The findings show that Temporal Deixis appears in three forms, namely absolute, relative, and duration, which are used to regulate the movement of the story’s time and influence the narrative rhythm. From Genette’s narratological perspective, time markers play a crucial role in creating analepsis (flashback) that forms the basis of the conflict and the dimensional shift experienced by the character Wira from the present to the past. Short duration markers, such as “two more minutes,” serve to slow down important scenes (stretch), while long duration markers act as narrative summaries (summaries). The main contribution of Temporal Deixis is seen in the formation of suspense as a “Time Trap,” where the delay of information and the use of countdowns create a sense of urgency and information imbalance, thereby increasing the reader’s emotional tension. This study confirms that time markers not only function linguistically, but also become an effective structural rhetorical tool in managing the reader's psychological experience, while expanding the study of pragmatics and narratology of thrillers. Penelitian ini meneliti peran Deiksis Temporal dalam membangun suspense atau ketegangan dalam novel thriller I’m Not Stupid dengan pendekatan kualitatif-deskriptif. Data dikumpulkan melalui close reading dan dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña untuk mengidentifikasi bentuk, fungsi naratif, dan kontribusi penanda waktu dalam alur cerita. Temuan menunjukkan bahwa Deiksis Temporal muncul dalam tiga bentuk, yaitu absolut, relatif, dan durasi, yang digunakan untuk mengatur pergerakan waktu cerita dan memengaruhi ritme naratif. Dari perspektif naratologi Genette, penanda waktu memainkan peran penting dalam menciptakan analepsis (kilas balik) yang menjadi dasar konflik dan perpindahan dimensi yang dialami tokoh Wira dari masa kini ke masa lalu. Penanda durasi yang singkat, seperti “dua menit lagi,” berfungsi memperlambat adegan penting (stretch), sedangkan durasi panjang berperan sebagai ringkasan naratif (summary). Kontribusi utama Deiksis Temporal terlihat pada pembentukan suspense sebagai “Jebakan Waktu,” di mana penundaan informasi dan penggunaan hitungan mundur menimbulkan rasa urgensi dan ketidakseimbangan informasi, sehingga meningkatkan ketegangan emosional pembaca. Penelitian ini menegaskan bahwa penanda waktu tidak hanya berfungsi linguistik, tetapi juga menjadi alat retoris struktural yang efektif dalam mengelola pengalaman psikologis pembaca, sekaligus memperluas kajian pragmatik dan naratologi thriller.